Identity of the limiting nutrient (N vs. P) affects the competitive success of mixotrophs - Fischer, R; HA, Giebel; Ptacnik, R (Marine Ecology Progress Series, 2017)
ABSTRACT: Empirical and theoretical evidence predicts that mixotrophic bacterivores dominate over specialized heterotrophic bacterivores and specialist photoautotrophs under conditions of high light and low loss rates. Here we extend this concept towards nutrient limitation and ask whether the identity of the limiting nutrient affects the competition of mixotrophs with their specialist competitors. Due to their photosynthetic machinery, mixotrophs should have higher cellular N contents than heterotrophs and, following this assumption, a higher demand for N. Conversely, heterotrophs, with their potential high growth rates compared to mixotrophs, may have a higher demand for P (?growth rate hypothesis?). Simplified, mixotrophs should be more prone to N-limitation, while heterotrophs should be more prone to P-limitation. We tested these predictions in artificial food webs studying the competitive success of mixotrophic bacterivores under a range of light intensities and loss rates and under either P- or N-limitation. Under low-light conditions, mixotrophs were more successful than heterotrophs under P-limitation, whereas the heterotrophs were more successful under N-limitation. At higher light intensity, mixotrophs had an advantage over photoautotrophs, due to the acquisition of nutrients ingested with prey. Overall, the effects of the limiting nutrient on the competitive success of mixotrophs were stronger under conditions already unfavorable for mixotrophs (low light). Further, our results suggest that communities dominated by mixotrophs might have low and relatively stable seston C:nutrient ratios. The results presented here supplement existing data well and help to define the ecological niche of mixotrophic protists.
Keywords: RCC744